Combined Effect of Dry Needling and Strain Counter Strain Technique in Myofascial Trigger Points of Upper Trapezius - Aqsa Aroob, Zarnain Khan, Adnan Ikram, Humera Tahir, Farwa Batool, Zainab Tehreem, Hafiza Rabia Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the combined effect of dry needling and strain counter strain technique in myofascial trigger points of upper. Method: This randomized control trial study was conducted at Male and Female physiotherapy ward, Outdoor, Mayo Hospital, Lahore. 28 patients who had complain of taut band, tenderness and referred pain and fulfill the inclusion criteria were enrolled in this research via non-probability consecutive sampling which randomized later and allocated to two equal groups. Group A (n=14) was experimental group treated by Dry needling and strain counter strain with baseline treatment. Group B (n=14) was a control group treated by Strain counter strain with baseline treatment. Baseline Physiotherapy Protocol that was given to every patient: Hot pack for 10 minutes, Trapezius muscle stretching, cervical muscle strengthening exercises (2 sets of 5 repetition each). Written consent was procured by every patient. Questioner that was used for data collection was Neck disability index (NDI) and other tools were Goniometer and Visual analogue scale (VAS). Results: Descriptive statistics showed that participants having mean age of 27 in group A and 35 in group B. Participants who received dry needling and SCS showed marked improvement as compare to group B. Statistically significant improvement found in all variables that were measured following the intervention (P<0.05). The pre-treatment mean score for NDI in group A was 3.50±0.519, while in group B was 3.64±0.497. After 8 weeks of treatment, the mean score in group A was 1.79±0.579, and in group B was 2.64±0.497 with the p value <0.0001 is less than 0.05 showed that Combined treatment effect of dry needling and Strain counter strain and control group treatment with strain counter strain only both are statistically significant in improving pain in Trigger points of the upper trapezius. Conclusion: It was concluded from the study that the combined technique of Dry needling and strain counter strain and only strain counter strain technique with baseline treatment both are effective in reducing pain and better active range of motion outcome as p=0.000 that p<0.005 showed both techniques are statistically significant but the mean value of Study group A is more than control group B, so Combined technique study group A is more effective than Strain counter strain technique with baseline treatment of control group B. Keywords: Dry needling, Strain counter strain, Visual analogue scale, Neck disability index.